Competitiveness Strategy in Facing Sustainable Economic Development on Social Economic Basis in Indonesia - Try Citra Puspitasari Lubis Citra (Journal of Asset Management and Public Economy (JAMPE), 2022)
Currently, what makes one of the human economies grow is economic development, especially in the new era, development is encouraged for the environmental domain, including in the socio-economic field. This paper aims to find out how the competitiveness strategy in facing sustainable economic development on the basis of socio-economic aspects sees Indonesia's position in the context of economic recovery, one of which is the problem from the economic side, namely economic growth and the social side, namely unemployment.